2020
DOI: 10.1002/tafs.10265
|View full text |Cite
|
Sign up to set email alerts
|

Muskellunge Spatial Ecology in the St. Louis River Estuary and Southwestern Lake Superior

Abstract: The St. Louis River estuary is a designated area of concern by the U.S. Environmental Protection Agency due to severe environmental degradation. The spatial ecology of Muskellunge Esox masquinongy, an indicator species, is uncertain within the estuary and the large, connected water body, Lake Superior. We collected genetic samples and used passive acoustic telemetry to track 60 adult Muskellunge in the St. Louis River estuary and southwestern Lake Superior for 15 months. Genetic analysis revealed that the rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Overall, these seasonal trends align with other seasonal movements of muskellunge reported in the literature, where high levels of activity and movement are observed in the fall and spring seasons compared to the summer (Gillis et al, 2010;Pankhurst et al, 2016;Schaeffer et al, 2020). Summer movements were the most restricted for muskellunge in this system and most resident to the middle section of the river once again, although further upstream than fish normally occupied in the fall, spring, and winter.…”
Section: Main Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…Overall, these seasonal trends align with other seasonal movements of muskellunge reported in the literature, where high levels of activity and movement are observed in the fall and spring seasons compared to the summer (Gillis et al, 2010;Pankhurst et al, 2016;Schaeffer et al, 2020). Summer movements were the most restricted for muskellunge in this system and most resident to the middle section of the river once again, although further upstream than fish normally occupied in the fall, spring, and winter.…”
Section: Main Findingssupporting
confidence: 88%
“…My research contributes to expanding our collective knowledge of the movement ecology of fishes in urban systems. I demonstrated that muskellunge seasonal movement patterns in relatively small and narrow urban waterbodies are similar to the movements of muskellunge in larger, lake or river systems (Dombeck 1979;Diana et al, 2015;Schaeffer et al, 2020;Hessenauer et al, 2021). My research also focused on under-studied, smaller-bodied freshwater fishes that are ecologically important but often receive relatively little conservation attention (Olden et al, 2007;Saddlier et al, 2013).…”
Section: Fundamental and Applied Contributionsmentioning
confidence: 73%
See 1 more Smart Citation
“…However, most of our tagged muskellunge moved to a different river segment once connectivity was restored in April (see section "Reach connectivity"), so it is unlikely muskellunge remain in a single region all year. This is consistent with Pankhurst et al (2016) who found that most of their tagged muskellunge (a study also conducted in the Rideau Canal) increased activity levels in spring and Schaeffer et al (2020) documented muskellunge exhibiting seasonal shifts in spatial use. We did not conduct surveys to evaluate persistent (winter) vegetation or woody debris, though these structures may have been present…”
Section: Drawdown Season Space Usesupporting
confidence: 87%
“…Most muskellunge that displayed increased activity were close to (within 100 mm) or longer than 700 mm, which in Ontario is generally considered size-at-first maturity (Casselman 2007). Larger spring movements by muskellunge, presumably driven by spawning temperatures, have indeed been documented in the Rideau River (e.g., Pankhurst et al 2016) and in other North American systems (e.g., Schaeffer et al 2020;Weber and Weber 2021).…”
Section: Potential Reproductive Movementsmentioning
confidence: 96%